1999
DOI: 10.1002/(sici)1097-4571(1999)50:3<254::aid-asi8>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Towards the identification of the optimal number of relevance categories

Abstract: In this paper, we are concerned with participants' confidence in their judgments of the relevance of bibliographic records to particular research questions. We describe an empirical investigation of the association between judges' confidence and the number of categories for a relevance rating scale. Participants rated the relevance of bibliographic records, and recorded their confidence in the relevance ratings. We hypothesize that confidence in relevance judgments is a function of the number of relevance cate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 17 publications
0
23
1
1
Order By: Relevance
“…Although Tang et al (1999) implied that a 7-point scale might provide users with the greatest confidence in making their relevance judgments, the analysis leading to that conclusion is flawed. The major problem is that the removal of data influences the frequency distribution of the relevance judgments on the various scales included in the study.…”
Section: Discussionmentioning
confidence: 99%
“…Although Tang et al (1999) implied that a 7-point scale might provide users with the greatest confidence in making their relevance judgments, the analysis leading to that conclusion is flawed. The major problem is that the removal of data influences the frequency distribution of the relevance judgments on the various scales included in the study.…”
Section: Discussionmentioning
confidence: 99%
“…Robertson (1981) argues that relevance should be treated as a continuous variable and hence, different levels of relevance should be incorporated in an evaluation model. Therefore, researchers have attempted to experiment with non-dichotomous relevance scales (Cuadra, 1967;Eisenberg, 1988;Janes, 1993;Spink et al, 1998;Tang et al, 1999). The study by Tang et al (1999) showed that a graded relevance scale with seven points led to the highest levels of confidence by the judges during their assessments.…”
Section: Relevance Assessmentsmentioning
confidence: 99%
“…Therefore, researchers have attempted to experiment with non-dichotomous relevance scales (Cuadra, 1967;Eisenberg, 1988;Janes, 1993;Spink et al, 1998;Tang et al, 1999). The study by Tang et al (1999) showed that a graded relevance scale with seven points led to the highest levels of confidence by the judges during their assessments. The additional benefit of using graded relevance scales is that a wider range of system effectiveness measures, such as Discounted Cumulative Gain (DCG), can be used (see Section 3.5).…”
Section: Relevance Assessmentsmentioning
confidence: 99%
“…In IIR, a range of scales points are provided (although it is most common to have five-or seven-point scales), a range of scale labels are provided (e.g., not at all, somewhat, very much) and a summative measure is usually not produced, which is why this type of scaling is often referred to as Likert-type. There is little guidance about the appropriate number of scale points, although some researchers have suggested that sevenpoints are optimal for eliciting relevance assessments [265]. What is clear is that an odd number of scale points allow subjects to select a mid-point, while an even number does not.…”
Section: Questionnairesmentioning
confidence: 99%